A comunicação como barreira à inclusão de alunos com deficiência visual em aulas de Física Moderna - Camargo, Eder Pires de [UNESP]; Nardi, Roberto [UNESP]; Correia, José Nivaldo [UNESP] (My University, 2010)
This article is part of a study that seeks to understand the main barriers to the inclusion of visually   impaired   students   in   learning   Physics.   Analyzing  modern physics classes, we examine the difficulties in communication between teachers and visually impaired students. Our study emphasizes the analyses of empiricalsensory and semantic structures of speech, indicating factors that may hamper  students’ understanding in the classroom. We recommend alternative procedures that aim to facilitate the effective participation of students with visual impairment in the communication process, such as:  elimination of the interdependent   audiovisual structure and the exploration of the communicational potentialities of a speech based on empirical structures whose accessibility does not depend on visual skills.

O presente artigo encontrase inserido dentro de um estudo que busca compreender as principais barreiras para a inclusão de alunos com deficiência visual no contexto do ensino de física. Focalizando aulas de física moderna, analisa as dificuldades comunicacionais entre licenciandos e discentes com deficiência visual. Para tal, enfatiza as estruturas empírica e semânticosensorial das linguagens utilizadas, indicando fatores geradores de dificuldades de acessibilidade às informações veiculadas. Recomenda, ainda, alternativas que visam dar condições à participação efetiva do discente com deficiência visual no processo comunicativo, das quais se destacam: a destituição da estrutura empírica audiovisual interdependente e a exploração das potencialidades comunicacionais das linguagens constituídas de estruturas empíricas de acesso visualmente independente.
Communication as a barrier to the inclusion of visually impaired students in Modern Physics classes
Keywords: Communication; Inclusion; Modern physics; Physics teaching; Visual impairment; Deficiência visual; Ensino de física; Física moderna; Comunicação; Inclusão